An update on the CardioMEMS pulmonary artery pressure sensor. (February 2019) - Ayyadurai, Puvanalingam; Alkhawam, Hassan; Saad, Muhammad; Al-Sadawi, Mohammed Adel; Shah, Niel N.; Kosmas, Constantine E.; Vittorio, Timothy J.
Heart failure (HF) is one of the most important healthcare issues due to its prevalence, high morbidity and mortality, as well as its economic burden. A shift in the healthcare model towards reducing inpatient hospitalizations might have a significant impact on HF-related costs and quality of life. Recently, wireless monitoring has begun to be an essential part of the management in the patient with HF. The CardioMEMS HF system is one of the best examples pertaining to the success in this field. This article will discuss the CardioMEMS HF system and the rationale behind its development.